Comparative approaches to biotechnology development and use in developed and emerging nations - Bas, Tomas Gabriel; Zhao, Jingyuan 1968- (Advances in bioinformatics and biomedical engineering (ABBE) book series, 2017)
"This book evaluates the importance of manufacturing biotechnological products around the world, highlighting a comparative analysis of public policies, technological policies, innovations, and marketing capability of developed and emerging nations"...